PENGUATAN CINTA AKSARA DAN BAHASA SUNDA MELALUI PROGRAM 40 HARI MENCINTAI KEARIFAN LOKAL DENGAN PENDEKATAN CONTENT AND LANGUAGE INTEGRATED LEARNING - Ade Aspandi; Annisa Fauziah Rahmah; Suci Tri Fuji Astuti; ardhian sahrul rhomadon; Miranda Nurfadillah (DEVELOPMENT: Journal of Community Engagement, 2025)
The Community Service Program (KKN) at Kertayasa 2 Elementary School in Sindangagung District aimed to foster students' love of Sundanese script and language through a Content and Language Integrated Learning (CLIL) approach. The initiative stemmed from the declining interest of young people in regional languages ​​due to the dominance of national and global languages. The research method used was qualitative, with data collection techniques including observation, interviews, and documentation of activities over a 40-day period. CLIL was implemented by integrating local wisdom into the learning process, enabling students to not only learn Sundanese linguistically but also understand its cultural values. The results showed that students were more enthusiastic about participating in the learning process, were able to write basic Sundanese script correctly, and were confident in using Sundanese in everyday communication within the school environment. Furthermore, teachers gained new experience in integrating content-based learning strategies with a linguistic approach, which resulted in increased variety in teaching methods. Overall, CLIL implementation has proven effective in increasing students' appreciation of Sundanese